(untitled) (Raparin Journal of Humanities (RJH), 2025)
Noise pollution is considered one of the environmental issues, and has a harmful effect on human health and the environment. The aim of this study is to determine and compare (Noise pollution level- NPL) of residential areas and main street. The NPL is recorded in eighteen points along Main Street and residential zone. Sound meters Equipment have been used to determine the NPL of residential zone and main street. NPL data were recorded in both seasons, summer and winter, on holidays such as Friday and working days from Saturday to Thursday, at three different times of the day: 7-9 am, 12-2 pm and 6-8 pm. The results illustrate that NPL is higher in summer than in winter because there are more human activities and working hours in summer. The average NPL on the main street in summer is 63 dB and in residential zones is 54 dB. However, in winter, the average overall NPL on the main street is 59dB in the residential area 44 dB. The NPL in the main street of the study area is higher than in the residential area. The main ways to reduce noise pollution are: using electronic motorcycles, quiet generator with determine places for electric power generators that are far from residential area and schools with interesting planting trees.